Comparison of 9th grade students’ physical activity levels during recess and regular class periods using objective measurement - Kretschmann, Rolf (Pedagogics, psychology, medical-biological problems of physical training and sports, 2016)
Purpose: to assess and compare secondary school students’ physical activity levels during recess and regular class periods using objective measurement. Material: The study sample consisted of 26 9th grade school students (M = 15.28 years, SD = 0.47) of a German secondary school. They wore the Actiheart the whole school day for one week. All students followed the same school schedule and participated in the same classes. 9th grade school students’ physical activity levels during recess and regular class periods were assessed using the physical activity monitoring device Actiheart, which validly and objectively measures physical activity. Results: total recess time physical activity levels accounted for M = 2.38 METs, whereas total class period time physical activity levels only reached M = 1.58 METs. This difference could be proven statistically significant. Conclusions: Total recess time accounts for significantly higher physical activity levels compared to total class period time and the overall time students spend in school, respectively.